Software quality management: Machine learning for recommendation of regression test suites - Owoc Mieczysław Lech; Stambulski Adam (Journal of Economics and Management)
Aim/purpose – This study aims to demonstrate machine learning (ML) applications to enhance software development quality management, specifically through optimizing regression test suites. This research aims to demonstrate how ML can predict and prioritize the most relevant regression tests based on software changes and historical testing data, thereby reducing unnecessary testing, assuring software quality, and leading to significant cost savings.